A Case Study On Business Strategy Formulation For An Industrial Semiconductor's Memory Divisions - Keong, Bun Hin (2005)
The objective of this paper is to formulate strategies needed by the company Infineon Technology Memory Business Division and focuses on four (4) areas to strengthen and reinforce the strategies associated to the company. The four areas are; maintain sustainability, generate profitability, improve productivity and develop growth in the highly competitive as well as achieving cost lower than annual price erosion in the memory chips.